Optimalisasi Peran Strategis PKK dalam Pencegahan Keterlambatan Bicara Anak Usia Dini di Kecamatan Padalarang - Wulandari Putri; Anira Anira; Wildan Alfia Nugroho; Andi Suntoda Situmorang; Rahma Sakina (Universitas Pendidikan Indonesia Kampus Purwakarta, 2022)
The Covid-19 pandemic had limited interactions and raised the potential of the increased use of gadgets. Those conditions might increase the prevalence of child speech delays considering the development of a child's speech requires two-way interactions. Speech delay in early childhood itself needs to be a concern for parents and the community because communication is one of the affecting aspects of a child's welfare. One of the components in the community that has a strategic role in reaching parents is the Family Welfare and Empowerment or known as PKK, team. Therefore, this Community Service was aimed to optimize the strategic role of Family Welfare and Empowerment (PKK) in preventing speech delays in early childhood. The activity was carried out in Padalarang District by involving twenty-four PKK team members and one PKK coordinator. The activity was carried out in two stages, including socialization and training. At the socialization stage, participants received exposure to the stages of language development according to age. At the training stage, participants received exposure and did hands-on practices related to the stimulation to improve early childhood language development. At the end of the activity, participants demonstrated an example of simple stimulation that can be given, such as reading aloud for children. The activity went well and was followed enthusiastically by the participants. Based on the interviews, participants gave positive responses. It is hoped that similar activities can be conducted continuously in the future.